2016
DOI: 10.1016/j.diabres.2016.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity patterns and gestational diabetes outcomes – The wings project

Abstract: PA levels are inadequate amongst this group of pregnant women studied i.e. those with and without GDM. However, a low-cost, culturally appropriate MOC can bring about significant improvements in PA in women with GDM. These changes are associated with improved glycemic control and reduction in adverse neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 29 publications
5
55
0
4
Order By: Relevance
“…There is a paucity of evidence on the association between GDM status and physical activity, with conflicting reports [25,26]. This study identified no differences in physical activity levels between women with and without GDM in the interval following GDM screening.…”
Section: Discussionmentioning
confidence: 62%
“…There is a paucity of evidence on the association between GDM status and physical activity, with conflicting reports [25,26]. This study identified no differences in physical activity levels between women with and without GDM in the interval following GDM screening.…”
Section: Discussionmentioning
confidence: 62%
“…The best type of intervention that should be recommended is unclear since all the successful programs used different exercise modalities in terms of intensity, type, duration and frequency. More recently, an initiative in India, the Wings Project, demonstrated that an intervention based on increasing total footsteps with pedometers was able to improve glycemic control in 151 women with GDM and reduce adverse neonatal outcomes in the more active tertiles when compared to their GDM counterparts in the upper tertiles of sedentary behaviour (323). Since no exercise-related injuries were experienced during pregnancy in all those studies, physical activity intervention seems safe to recommend.…”
Section: Management: Healthy Behaviour Interventionsmentioning
confidence: 99%
“…A pedometer was provided to all women in order to track the number of steps taken daily. Analysis of physical activity patterns in a subgroup of women with GDM followed up under the MOC has been discussed in a previous publication …”
Section: Methodsmentioning
confidence: 99%